Application of Statistical Design to Assess the Critical Process Parameters of Ethanol Injection Method for the Preparation of Liposomes - Bhattacharyya, Sayani; Sogali, Bharani S (Dhaka University Journal of Pharmaceutical Sciences, 2019)
In the present study custom screening design was employed to observe the effect of four critical process parameters on particle size and polydispersity index of the liposomal formulation made by ethanol injection method. The four process parameters selected were lipid ratio, rate of injection, phase volume ratio and rotational speed of magnetic stirring. Eight different liposomal formulations were prepared using the design. The formulations were subjected to particle size analysis. The analysis was done at a significance level p<0.05 and found that the process parameters had significant effect on the particle size and polydispersity index of the formulations. The design was optimized for the individual responses with an overall desirability of more than 50%. Three batches of liposomes were formulated at optimized process parameters which matched the target as predicted by the design. Therefore, it can be concluded that the design was effective in production of nano sized stable monodisperse liposomes by ethanol injection method. Dhaka Univ. J. Pharm. Sci. 18(1): 103-111, 2019 (June)